Reasons for alcohol use and non-use by underage U.S. autistic youth: A qualitative study. (January 2023) - Rothman, Emily F; Graham Holmes, Laura; Brooks, Dani; Krauss, Shari; Caplan, Reid
This study describes the views and experiences of autistic youth about alcohol, including reasons for use and nonuse. We conducted 40 semi-structured interviews with autistic youth aged 16–20 years old. Of these, 20 had consumed alcohol in the past year. We used an inductive content-based analysis approach. Youth were deliberate about their choices to use, or abstain from, alcohol. Some conducted their own background research on the effects of alcohol, while others took a very measured approach to drinking and paced their alcohol consumption during drinking episodes with care. Reasons not to drink included fear of developing alcohol addiction, not liking the taste of alcohol, concern about alcohol interacting with prescribed medications, as well as the desire to avoid hangover, disinhibition, or other negative effects. On the contrary, youth had some positive alcohol expectancies: non-autistic people are more accepting when drinking, alcohol helps autistic people cope with problems, irritability, boredom, and sensory processing challenges, and helps them fit in. Results reveal that alcohol use disorder in autistic adults could have its roots in underage experiences that provide temporary relief from social anxiety, feeling socially isolated, and challenges with sensory processing. The development of evidence-based youth alcohol prevention strategies for autistic youth may be an important next step. Lay abstract: What is already known about the topic? Hazardous alcohol use is when a person's drinking puts them at increased risk for negative events (e.g. health problems or car crashes). Some studies show that autistic people may be at greater risk for hazardous alcohol use than non-autistic people, while other studies have found that hazardous alcohol use is less common among autistic people than non-autistic people. We need to learn why autistic underage youth choose to drink alcohol or not. The goal of this study was to learn from US autistic youth about their attitudes and behavior related to alcohol. Forty autistic youth aged 16–20 years old were interviewed. What this article adds? Youth described several reasons why they choose to drink alcohol, including feeling like non-autistic people are more accepting when drinking, that it puts them in a less irritable or bored mood, helps them cope with problems, and helps them fit in. Reasons for not drinking alcohol include worries about becoming addicted, medication interactions, not liking the taste, fear of experiencing hangover and other health problems, and concern about acting foolish when drunk. Implications for practice, research, or policy Results reveal that hazardous alcohol use in autistic adults could have its roots in underage experiences that give autistic youth temporary relief from social anxiety, feeling lonely, and challenges with sensory processing. Right now, there are no evidence-based alcohol prevention programs in the United States for autistic people. One or more such programs may be needed. The results from this study could be used to adapt existing programs for non-autistic youth to the unique needs and risk factors of autistic youth.